Mentoring Across Differences - Nora Yusuf Osman; Barbara Gottlieb (Association of American Medical Colleges, 2018)
Introduction Effective mentoring can contribute to wellness and career growth and satisfaction. However, the same social forces and interpersonal dynamics affecting all relationships can compromise mentoring relationships. This is especially true when there are issues that are compounded by structural disadvantage due to racism, gender bias, social class, and other discriminatory factors. The Mentoring Across Differences (MAD) sessions are a workshop designed to develop and nurture skills, tools, self-awareness, and mindful practice in mentors and mentees. The workshop encourages participants to gain confidence in navigating differences across a variety of domains. Methods We designed interactive sessions for faculty as part of a nine-part training series on mentoring in an academic setting. Teaching methods drew from adult learning theory. We used cases distilled from real teaching and mentoring experiences to trigger discussion and activate emotion and intrinsic motivation. Participants' prior knowledge and experience were drawn on to cocreate knowledge through small-group peer learning. Results As part of a course, 167 participants completed the sessions; several hundred more people participated in them in faculty development venues. Participants highly rated the open discussions regarding differences and enhanced awareness of their assumptions, specifically highlighting knowledge and tools addressing bias in their roles as mentors and teachers. Discussion The MAD sessions function both as an important module in a comprehensive mentoring curriculum and as stand-alone sessions. They fill a critical need of faculty and training institutions to explore difference in order to foster diversity and inclusion.